2017
DOI: 10.1371/journal.pone.0184969
|View full text |Cite
|
Sign up to set email alerts
|

Low serum level of miR-485-3p predicts poor survival in patients with glioblastoma

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs that play critical roles in human malignancies and can be used as biomarkers for cancer. Until now, a number of biomarkers for prognosis of glioblastoma (GBM) have been reported in tumor tissues but only a few biomarkers in circulating fluid. Using a custom microarray, we previously identified 19 differentially expressed miRNAs in serum of patients with GBM. In this study, we investigated whether 3 of the 19 miRNAs in serum could be used as prognostic biomarkers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…MiR-485 is underexpressed in a variety of human cancers and exerts tumor-suppressive effects during cancer progression. [42][43][44][45][46][47][48][49][50][51][52] Herein, our results confirm that miR-485 is downregulated in both cervical cancer tissues and cell lines. Functionally, miR-485 was found to perform tumorsuppressive activities and was implicated in the control of malignant behavior of cervical cancer cells.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MiR-485 is underexpressed in a variety of human cancers and exerts tumor-suppressive effects during cancer progression. [42][43][44][45][46][47][48][49][50][51][52] Herein, our results confirm that miR-485 is downregulated in both cervical cancer tissues and cell lines. Functionally, miR-485 was found to perform tumorsuppressive activities and was implicated in the control of malignant behavior of cervical cancer cells.…”
Section: Discussionsupporting
confidence: 72%
“…This analysis indicated that miR-485 contains a putative binding site for SNHG7 ( Figure 3B). MiR-485 is reported to be downregulated, and to exert tumor-suppressive effects in multiple human cancer types; [42][43][44][45][46][47][48][49][50][51][52] consequently, this miRNA was chosen for subsequent experiments. To test whether miR-485 can directly interact with the binding site in SNHG7, we generated the luciferase reporter plasmids harboring either the wild-type or mutant miR-485-binding site.…”
Section: The Snhg7 Knockdown Inhibits the Malignant Characteristics Omentioning
confidence: 99%
“…For example, miR-485 is underexpressed in glioblastoma tissues, cell lines and blood serum. In addition, decreased miR-485 expression is correlated with poor progression-free survival and overall survival in patients with glioblastoma (18,19). In gastric cancer, the downregulation of miR-485 is strongly associated with tumor size, invasion depth, lymph node metastasis and tumor-node-metastasis (TNM) stage.…”
Section: Discussionmentioning
confidence: 99%
“…miR-485 is aberrantly expressed in several types of human cancer, including glioblastoma (18,19), gastric cancer (20) and lung adenocarcinoma (21). However, to the best of the authors' knowledge, the expression pattern, biological functions and underlying mechanisms of miR-485 in cervical cancer have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There are no literature reports of an involvement of miR-502-5p in CNS tumors, but it has been found up-regulated in the serum of patients with subarachnoid hemorrhage (SAH) ( Lai et al, 2017 ). Other Authors have conducted studies on serum, plasma, and whole blood samples of Glioblastoma or Low-grade glioma patients to isolate freely circulating, cellular and exosomal microRNA signatures ( Gozé et al, 2017 ; Regazzo et al, 2016 ; Roth et al, 2011 ; Wang et al, 2017b ). Although all signatures showed promising results, they could not correlate to survival.…”
Section: Discussionmentioning
confidence: 99%